Strontium-doped bioactive glass/PDA functionalized polyetheretherketone with immunomodulatory property for enhancing photothermal clearance of Staphylococcus aureus - Su, Xinjin; Lyu, Zhuocheng; Wu, Yuezhou; Gu, Yue-Huan; Huo, Shicheng; Zhou, Chun (Materials & design, 2023)
[Display omitted] •SPK-SP was fabricated on PEEK implants surface by a simple strategy at ambient temperature.•SPK-SP showed multifunction of immune-modulatory and antibacterial and superior photothermal effect.•SPK-SP exhibited excellent antibacterial and anti-biofilm efficiency in vitro and in vivo.•SPK-SP favored macrophage polarization to M2 anti-inflammatory microenvironment to promote tissue repair following infection. The infection of implants following orthopedic surgery is a “catastrophic” surgical complication, particularly when biofilms form, protecting bacteria from antibiotics as well as the patient’s immune system. To address the current difficulties in treating biofilm infections, we fabricate a functional strontium doped bioactive glass nanoparticles (Sr-BGNs)-instructed orthopedic implant composed of PEEK, Sr-BGNs and polydopamine (PDA). In addition to destroying the permeability and integrity of MRSA biofilm, PDA also endowed PEEK substrate with effective antibacterial ability when exposing to near-infrared (NIR) irradiation. The NIR mediated photothermal disruption of biofilms contributed to the advanced antibacterial therapy, which has been validated by the efficient eradication of methicillin-resistant Staphylococcus aureus strains (MRSA) biofilm in vitro and in vivo. Notably, the engineered implants exhibit satisfactory cytocompatibility. In addition, Sr ions released from Sr-BGNs inhibited the expression of inflammatory genes, thereby providing a superior environment for tissue repair after infection clearance. The synergistic effect of photothermal effect and immunomodulatory property might have promising applications for preventing perioperative infection and tissue repair after infection.